The effect of heating on the antioxidants content in edible oil - Premanand, K. (2010)
There are many types edible oils with various brand found in the market. The types of oils involved in the analysis for the antioxidants content were palm oil, olive oil, canola oil, sunflower oil, soy bean oil, corn oil, gingerly oil, rice bran oil, mixed oil and ayurvedic oil. The method used to evaluate the amount antioxidants in this study was 2, 2-diphenyl-1-picrylhydrazyl (DPPH). In this test, the scavenging of the DPPH radicals was followed by monitoring the decrease in absorbance at 515 nm. Heating the oil samples to various temperatures shows negative effect on the antioxidants content. The antioxidants content in all types of oils showed decreasing pattern when subjected to heat. The sample with highest antioxidants content at the temperature 180 oC is corn oil, followed by palm oil, sunflower oil, olive oil, canola oil, ayurvedic oil, rice bran oil, mixed oil, soy bean oil and lastly gingerly oil. Therefore, corn oil is the most suitable type of oil for high temperature cooking such as frying.